The Effect of the Board of Commissioners, Audit Committee, Company Size on Tax Avoidance with Leverage as an Intervening Variable - Pamungkas, Fuad Jaka; Fachrurrozie, Fachrurrozie (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of the board of commissioners, audit committee, company size on tax avoidance with the intervening variable in the form of leverage. The population of this research is 48 properties and real estate listed on the IDX in 2015-2018. The sample selection is done using the purposive sampling method and produces 60 units of analysis. The method used to analyze the data is descriptive statistics and path analysis with the IBM SPSS 21 software. This study shows the results between the board of commissioners, the audit committee, leverage has a significant positive effect on tax avoidance. Company size does not affect tax avoidance. The board of commissioners and company size have no effect on leverage. The audit committee has a significant negative effect on leverage. Leverage succeeded in intervening in the influence of the audit committee but failed to intervene in the effect of the board of commissioners and company size on tax avoidance. This study concludes that companies with boards of commissioners and audit committees tend to increase the efficiency of their tax burden. The audit committee uses leverage to increase the efficiency of the tax burden. This research is able to strengthen and develop from existing research related to tax avoidance. Keywords: Board of Commissioners; Audit Committee; Company Size; Leverage; Tax Avoidance